2013
DOI: 10.1186/1475-2875-12-214
|View full text |Cite
|
Sign up to set email alerts
|

CYP450 phenotyping and metabolite identification of quinine by accurate mass UPLC-MS analysis: a possible metabolic link to blackwater fever

Abstract: BackgroundThe naturally occurring alkaloid drug, quinine is commonly used for the treatment of severe malaria. Despite centuries of use, its metabolism is still not fully understood, and may play a role in the haemolytic disorders associated with the drug.MethodsIncubations of quinine with CYPs 1A2, 2C9, 2C19, 2D6, and 3A4 were conducted, and the metabolites were characterized by accurate mass UPLC-MSE analysis. Reactive oxygen species generation was also measured in human erythrocytes incubated in the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 20 publications
1
9
1
Order By: Relevance
“…It is worth mentioning that the presented data are in certain contrary to the reports concerning (bio)transformation of quinine and its derivatives [18]. Following [18], these compounds are transformed to demethyl and dearomatic products and to hydroxyl derivatives with hydroxyl group attached to another position in carbon ring of quinine than that indicated in our experiments.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…It is worth mentioning that the presented data are in certain contrary to the reports concerning (bio)transformation of quinine and its derivatives [18]. Following [18], these compounds are transformed to demethyl and dearomatic products and to hydroxyl derivatives with hydroxyl group attached to another position in carbon ring of quinine than that indicated in our experiments.…”
Section: Discussioncontrasting
confidence: 56%
“…Following [18], these compounds are transformed to demethyl and dearomatic products and to hydroxyl derivatives with hydroxyl group attached to another position in carbon ring of quinine than that indicated in our experiments. This is obvious as (bio)transformation pathway occurring in living organisms is catalyzed by enzymes and often does not comply with the rules of classical organic synthesis.…”
Section: Discussionmentioning
confidence: 79%
“…43 Quinine can undergo various cytochrome p450-dependent structural modifications that could result in reactive intermediates capable of linking to protein and acting as haptens to trigger an immune reaction. [48][49][50] A response to quinine-conjugated proteins could explain hapten (quinine)-specific antibodies typically found in patients with quinineinduced thrombocytopenia. 43 The striking difference in serologic behavior of these antibodies, and those that bind to platelets and cause thrombocytopenia, suggests that the two types of antibodies may be induced in quite different ways.…”
Section: Discussionmentioning
confidence: 99%
“…Since chloroquine was introduced after World War II supplanting quinine as first-line treatment of uncomplicated malaria, there has been an observed decrease in BWF [ 1 ]. A recent report suggested that metabolism of quinine by the cytochrome P450 3A4 enzyme may be responsible for increasing oxidative stress within erythrocytes, making these cells more vulnerable to haemolysis in those with malaria and/or G6PD deficiency [ 13 ]. The role of artemisinin compounds in such potential oxidant acute haemolysis remains poorly understood [ 14 ].…”
Section: Discussionmentioning
confidence: 99%